Effects of High‐Fructose Corn Syrup Addition to Broiler Diets on Performance, Carcass Yield, Visceral Weights, Gut pH and Some Blood Parameters - Gökhan Şen; Mehmet Demirci; Şevket Evci; Ali Şenol; Mehmet Akif Karsli (Veterinary Medicine and Science)
ABSTRACT Background This study hypothesizes that using different amounts of high‐fructose corn syrup (HFCS) in broiler diets may improve performance. Objectives This study aimed to determine the effects of HFCS added to broiler diets on performance, cecum pH and some biochemical parameters. Methods A total of 120 Ross 308 chicks at the age of 0 day were divided into three main groups with four subgroups each. The groups consisted of a control (CON), low‐HFCS and high‐HFCS groups. The CON group received a diet containing no HFCS, the low‐HFCS diet contained 50 mg/kg HFCS, and the high‐HFCS diet contained 100 mg/kg HFCS. Body weight gain, feed consumption, carcass weight, visceral weight and cecum pH values were examined as performance parameters. Blood samples were taken at the end of the experiment and used to spectrophotometrically determine triglyceride, total cholesterol, high‐density lipoprotein (HDL‐CHO), low‐density lipoprotein (LDL‐CHO), glucose (GLU), creatinine (CRE), uric acid and insulin concentrations, as well as aspartate aminotransferase and alanine aminotransferase activities and oxidative stress markers. Proinflammatory cytokine levels were measured using ELISA test kits. Results Feed consumption and body weight gain of the high‐HFCS group decreased (p < 0.01). The feed conversion rate was negatively affected in both HFCS groups compared to the CON group (p < 0.01). The carcass yields of the groups linearly decreased with the increase of HFCS (p < 0.001). Serum LDL cholesterol (p < 0.05) and GLU (p < 0.01) levels were significantly lower in the HFCS groups than the CON. Serum CRE levels were higher in the low‐HFCS group compared to the other groups (p < 0.001). The oxidative stress index (OSI) levels were lower in the low‐HFCS group than the CON group (p < 0.05). Conclusion The addition of 100 mg/kg HFCS to broiler diets negatively affected performance parameters, but HFCS supplementation positively affected biochemical parameters. In particular, low‐HFCS supplementation decreased the OSI, indicating that it could possibly reduce oxidative stress. Accordingly, HFCS could be added to broiler diets at a level of 50 mg/kg.